A Case Report: A Duodenal Polyp with Gastric Foveolar Metaplasia and Dysplasia - Battah, khairat; Battah, Arwa; Malkawi, Ruba; Alkhreisat, mohammad (Jordan Medical Journal, 2025)
Duodenal polyps are a common finding during endoscopic investigations, typically representing benign conditions such as regenerative or reactive changes and gastric heterotopia. Some regenerative changes can present as metaplasia, particularly of the gastric foveolar epithelial type. However, adenomatous changes associated with gastric foveolar epithelium are rare. This article presents a case of a gentleman whoexperiened dyspepsia and dysphagia. Endoscopy revealed a polypoid lesion that exhibited low-grade dysplasia with gastric foveolar metaplasia upon histopathologic examination. This case supports the hypothesis that metaplastic epithelium in the duodenum can serve as a precursor to neoplastic processes, underscoring the importance of vigilant surveillance and the necessity for further molecular investigations.